An Evaluation of the United Kingdom Motor Neuron Disease Nurses and Allied Health Professionals (UK MND NAHP) Workforce: A Census - Isaac Chau; Ethan Stoker; Jessica Gill; Judith Newton (PLoS ONE, 2025)
According to the National Institute for Health and Care Excellence, motor neuron disease assessment and management should be a coordinated, clinic-based, multidisciplinary team approach. However, the wellbeing, work experiences, and the alignment with national frameworks and standards of the motor neuron disease (MND) nurses and allied health professionals’ workforce are severely underreported and under-researched within the literature. Therefore, this report aimed to capture the workforce and their alignment with national frameworks and standards, and to assess their experiences working as an MND health care professional. A pragmatic research paradigm and a mixed methods approach was employed using a cross-sectional questionnaire survey to collect, compare, and interpret quantitative and qualitative data points. Data was gathered under the remit of an audit and service evaluation under NHS Lothian. Demographics data and work-related characteristics were collected. Job experience and wellbeing were collected using Likert scales and open-ended questions. The level of burnout was assessed using the validated tool, the Burnout Assessment Tool (BAT). Compliance with national frameworks were based on the NICE guidelines and the Scottish MND Advanced Clinical Nurse Specialist Pillars of Practice Competencies. 64 HCPs completed the questionnaire, with the majority of respondents from England (54.7%) and Scotland (35.9%). Education level was mainly having a Bachelors (or equivalent) degree (40%) or a Masters (or equivalent) degree (31%), with the remaining having a diploma-based qualification (29%). The analysis revealed three key themes: the importance of the multi-disciplinary team (MDT), the roles and the level of competencies, and the benefits and challenges in providing direct care. This was associated with 14% and 12% of respondents being at medium and high risk of burnout, respectively. This report highlighted the importance of a collaborative MDT to support the needs of patients, their carers/ family members and HCPs themselves. The workforce found the flexibility, autonomy, and variety within their role beneficial where almost 80% of the respondents engaged in 8 of the 15 competencies. The benefits of providing direct care were found to be associated with feeling valued by the patients, their carers/ family members, and the core and extended MDT, and feeling satisfied about their work. The perceived challenges of providing direct care involved isolation, lack of direct funding, and a high caseload with complex needs and not enough time to provide quality care. It is recommended that a national competency programme or a Masters level course in MND care should be developed to maintain the quality of care, and future research should aim to evaluate the entire workforce longitudinally, address organisational barriers, and explore burnout preventative strategies to maintain a resilient workforce.